2014
DOI: 10.1103/physreva.90.043636
|View full text |Cite
|
Sign up to set email alerts
|

Three-body parameter for Efimov states inLi6

Abstract: . (2014) 'Three-body parameter for E mov states in 6Li. ', Physical review A., 90 (4). 043636.Further information on publisher's website:http://dx.doi.org/10.1103/PhysRevA.90.043636Publisher's copyright statement:Reprinted with permission from the American Physical Society: Bo Huang (), Kenneth M. O'Hara, Rudolf Grimm, Jeremy M. Hutson, and Dmitry S. Petrov (2014) 'Three-body parameter for E mov states in 6Li.', Physical review A., 90 (4), 043636. c 2014 by the American Physical Society. Readers may view, brow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 63 publications
4
41
0
Order By: Relevance
“…The present analysis also does not consider Efimov resonance shifts arising from finite temperature. This is in contrast to the recent studies in the homonuclear gases of Cs and Li atoms [47,49,50], which have shown that such effects need to be taken into account in order to accurately determinate the Efimov resonance positions. At the same time, the scaling factor of the second Efimov period lies well within the universal predictions, and experimental demonstration of deviations from the universal law, if any, will require access to lower temperatures and improved control over the magnetic field systematics.…”
Section: Scaling Of Licscs Efimov Resonancesmentioning
confidence: 62%
“…The present analysis also does not consider Efimov resonance shifts arising from finite temperature. This is in contrast to the recent studies in the homonuclear gases of Cs and Li atoms [47,49,50], which have shown that such effects need to be taken into account in order to accurately determinate the Efimov resonance positions. At the same time, the scaling factor of the second Efimov period lies well within the universal predictions, and experimental demonstration of deviations from the universal law, if any, will require access to lower temperatures and improved control over the magnetic field systematics.…”
Section: Scaling Of Licscs Efimov Resonancesmentioning
confidence: 62%
“…Converting toā (n) using Eq. (4), yields theā (n) values reported in the table paper [35] that analyzed the experimental data-"compromised" by the fact that the three s-wave scattering lengths are slightly different. Interestingly, though, the value ofā (2) /r 6 agrees with what is reported in Table 2.…”
Section: Discussionmentioning
confidence: 97%
“…The results were reanalyzed in Ref. [38] based on the UZR theory. For the very large length scale of an excited Efimov state, finite-range corrections can be expected to be very small.…”
Section: B Excited-state Efimov Resonance In 6 LImentioning
confidence: 99%
“…An extension of the theory has been applied in Ref. [38] to analyze observations of an excited-state Efimov resonance in the three-fermion system of 6 Li [14]. A further extension has been presented in Ref.…”
Section: Introductionmentioning
confidence: 99%